2014
DOI: 10.1017/thg.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Relationships Between Change in Weight and Insulin Resistance: The Healthy Twin Study

Abstract: We aimed to investigate the association between weight change from 20 years of age and insulin resistance (IR), and genetic and environmental relationships between these traits. In 594 Korean twins and family members (209 men, 385 women, 44.0 ± 10.8 years old), the percentage of weight change was calculated using self-reported body weight at 20 years of age and currently measured bodyweight. IR traits were assessed using fasting plasma glucose and insulin, the homeostasis model assessment of IR index (HOMA-IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(53 reference statements)
0
2
0
2
Order By: Relevance
“…Therefore, certain individuals with a particular genetic blueprint may be more likely to eat to excess when confronted by the multiple eating opportunities in our environment and consequently gain more weight. The contribution of other genetic factors, such as conditioned insulin resistance (Song et al, ), adiponectin and leptin (Liu et al, ), has also been demonstrated. Further investigations are needed to correctly address the influence of genetic background on the prevalence of obesity in our area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, certain individuals with a particular genetic blueprint may be more likely to eat to excess when confronted by the multiple eating opportunities in our environment and consequently gain more weight. The contribution of other genetic factors, such as conditioned insulin resistance (Song et al, ), adiponectin and leptin (Liu et al, ), has also been demonstrated. Further investigations are needed to correctly address the influence of genetic background on the prevalence of obesity in our area.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been explained as an imbalance between energy intake and expenditure, influenced by a complex interplay of genetic, social, and environmental factors . Observations on many wild small mammal species have suggested that, contrary to humans, they have a strong regulation mechanism that allows them to avoid the risk of becoming obese .…”
Section: Introductionmentioning
confidence: 99%
“…Os genes podem influenciar os fenótipos que envolvem variados estados de doenças, os fenó-tipos são relevantes para os comportamentos e respostas como modificadores das exposições ambientais, e estes últimos podem modificar as marcas epigenéticas e a função dos genes. (Song, 2014) A relação ambiente e Genes interagem podendo formar um ciclo de fatores que aumentam a predisposição à síndrome metabólica. Desse modo, as variações genéticas e certos fatores ambientais influenciam para desencadear e manter quantidades significativas de distúrbios no organismo.…”
Section: Teoria Do Percurso De Vidaunclassified
“…Alterações que refletem a prevalência de um ambiente imediatista e podem influenciar estratégias de percursos de vida como respostas aos fatores de riscos (Giudice, Del, Gangestad e Kaplan, 2015;Kellermann, 2001;, sendo preditivos relevantes que estão associados aos riscos das doenças crônicas e transtornos comportamentais. (Song, 2014;Baranowskv et al, 1998;Yehuda et al, 2014)…”
Section: Introductionunclassified